Immune Checkpoint Inhibitors in Human Glioma Microenvironment - Ghouzlani, Amina; Kandoussi, Sarah; Tall, Mariam; Reddy, Konala Priyanka; Rafii, Soumaya; Badou, Abdallah (Frontiers in Immunology, 2021)
Gliomas are the most common primary brain tumors in adults. Despite the fact that they are relatively rare, they cause significant morbidity and mortality. High-grade gliomas or glioblastomas are rapidly progressing tumors with a very poor prognosis. The presence of an intrinsic immune system in the central nervous system is now more accepted. During the last decade, there has been no major progress in glioma therapy. The lack of effective treatment for gliomas can be explained by the strategies that cancer cells use to escape the immune system. This being said, immunotherapy, which involves blockade of immune checkpoint inhibitors, has improved patients’ survival in different cancer types. This novel cancer therapy appears to be one of the most promising approaches. In the present study, we will start with a review of the general concept of immune response within the brain and glioma microenvironment. Then, we will try to decipher the role of various immune checkpoint inhibitors within the glioma microenvironment. Finally, we will discuss some promising therapeutic pathways, including immune checkpoint blockade and the body’s effective anti-glioma immune response.